Effects of mixture design variables on rubber bitumen interaction properties of dry mixed rubberized asphalt mixture - Bibi Farouk, Abdulwarith Ibrahim (Springer, 2017)
The utilization of crumb rubber in asphalt mixture has significantly evolved in the past few decades. However, the modification through dry process method has been a far less popular compared to the wet process due to a few drawbacks that affect its performance. One such concern that is often ignored by researcher relates to the rubber–bitumen interaction that causes swelling of the rubber particles within compacted asphalt mixture. Rubber–bitumen interaction refers to the absorption of bitumen particularly the maltenes fraction by rubber particles. This study investigated the effects of mixture design variables on the rubber–bitumen interaction and properties of rubberized asphalt mixtures fabricated through the dry method. The effects of rubber–bitumen interaction at different rubber sizes, bitumen contents, and curing periods were investigated using the “Basket Drainage Method”. While, the mechanical properties of rubberized asphalt mixtures were measured using resilient modulus and dynamic creep tests. Four types of gyratory compacted specimens of a dense grade mixture of asphaltic concrete were fabricated. The four specimen types comprised a control specimen without rubber and three other specimens with 2 % crumb rubber of varying sizes (1.18, 3.35 and 5.0 mm). Results showed that higher rubber–bitumen interaction can be obtained with the use of fine rubber size and high bitumen content, thus exhibiting greater rubber swelling particularly in the first 4 h of curing. Specimen with fine rubber can be easily compacted to achieve the target density which shows consistency in the volumetric properties. The addition of crumb rubber reduces the resilient and creep modulus of asphalt mixtures compared to the control mix. However, by initiating the rubber swelling extensively prior to compaction can possibly improve the compatibility and volumetric properties, thus enhancing better performance of the rubberized asphalt mixtures.